1996
DOI: 10.1111/j.1476-5381.1996.tb15675.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the negative inotropic effects of 17β‐oestradiol in human isolated myocardial tissues

Abstract: 1 The aim of the present study was to evaluate the effects of 17,B-oestradiol in human myocardium. The effects of 17#f-oestradiol, progesterone and testosterone on force of contraction were investigated in electrically driven isolated atrial trabeculae and ventricular papillary muscles from human hearts in the presence and absence of Bay K 8644, a calcium channel agonist. In addition, the effects of 17,Boestradiol, progesterone and testosterone on binding of [3H]-PN 200 110 were assessed in membranes prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 31 publications
3
19
1
Order By: Relevance
“…Another new finding of the present investigation was the demonstration that progesterone infusion did not significantly affect left ventricular dPÏdtmax, which in the absence of changes in heart rate, arterial blood pressure and filling pressures of the heart indicated no change in ventricular contractility (Furnival et al 1970). This finding is also supported by previous reports showing that progesterone or its derivatives had no significant effect on contractility of isolated human heart muscles (Sitzler et al 1996) or guinea-pig atria (Temma et al 1983). However, one report in isolated rabbit heart found that progesterone induced coronary vasoconstriction and a negative inotropic effect (Raddino et al 1989).…”
Section: Discussionsupporting
confidence: 89%
“…Another new finding of the present investigation was the demonstration that progesterone infusion did not significantly affect left ventricular dPÏdtmax, which in the absence of changes in heart rate, arterial blood pressure and filling pressures of the heart indicated no change in ventricular contractility (Furnival et al 1970). This finding is also supported by previous reports showing that progesterone or its derivatives had no significant effect on contractility of isolated human heart muscles (Sitzler et al 1996) or guinea-pig atria (Temma et al 1983). However, one report in isolated rabbit heart found that progesterone induced coronary vasoconstriction and a negative inotropic effect (Raddino et al 1989).…”
Section: Discussionsupporting
confidence: 89%
“…Coronary dilation may also explain the antiischemic effect of 17β-estradiol in women (Rosano et al 1993). The heart muscle may also be a target organ for estrogens (Jiang et al 1992b;Eckstein et al 1994;Sitzler et al 1996). In male guinea-pig cardiac myocytes an inhibition of calcium inward current and a shortening of action potentials occurs (Jiang et al 1992b).…”
Section: Introductionmentioning
confidence: 99%
“…In male guinea-pig cardiac myocytes an inhibition of calcium inward current and a shortening of action potentials occurs (Jiang et al 1992b). In human atrial and ventricular preparations a negative inotropic effect of 17β-estradiol has been reported (Sitzler et al 1996). We examined male rat ventricular myocytes and focussed our investigations on 17β-estradiol-induced effects on outward currents.…”
Section: Introductionmentioning
confidence: 99%
“…In rabbit papillary muscle, the chronic administration of 17␤-estradiol at Ͻ10 Ϫ6 M, but not acute administration, reduced isometric force [17]. In contrast, the effects of acute dosage with high concentrations has been reported in the muscle: 10 Ϫ5 M for the reduction in cytosolic Ca 2ϩ and inward Ca 2ϩ current of guinea pig cardiac myocytes [18], and ϳ10 Ϫ6 M for the negative inotropic effect on human myocardium [19]. Also in the present experiments using isolated frog muscle, the effective concentration of 17␤-estradiol was 10 Ϫ5 M to allow the acute actions to be clearly observed.…”
Section: Discussionmentioning
confidence: 99%